C455R notch3 mutation in a Colombian CADASIL kindred with early onset of stroke (2002)
ABSTRACT: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by mutations in the notch3 epidermal growth factor–like repeats. A Colombian kindred carries a novel C455R mutation located in the predicted ligand-binding domain. Stroke occurred in the patients at an unusually early age (median age: 31 years) in comparison to the more frequent onset in the fourth decade of life in other CADASIL populations, including a second Colombian kindred with an R1031C mutation.